Efforts To Improve The Health Of Mother And Baby Through The Utilization Of Moringa Leaves As Food Material In Harjosari Ii Village, Medan Amplas District - Nurbaiti; Darti Nur, Afi; Achmad Yasmin, Bedegeil; Mia, Barus; Dani, Rahmadhani; Sari Ratna, Dewi; Audina Mitha, Ramadani (Talenta Publisher, 2021)
Human growth and development is very important because human will never develop without development and growth. The factors that influence human growth and development are not widely known, one of which is the fulfillment of balanced nutrition. Inadequate nutritional intake will have an impact on the growth and development of children under five years of age for long-term, which are permanent and difficult to repair. Likewise, maternal health will affect motherâ€™s activities in taking care of family. Complementary feeding (MPASI) and food for mothers can be made from local ingredients so that children under five years of age get adequate nutritional intake according to their age. Moringa leaf is an ingredient that is rich in macro and micro nutrients. The high nutritional value in Moringa leaves can be used to meet the nutritional needs of breastfeeding mothers and children under five years of age in their infancy (Aminah et al, 2015). The objective of this community service was to improve the health status of mothers and children through utilization of Moringa leaves. This activity was carried out on September 14, 2020 at Posyandu Melati 2, Harjosari II Village, Medan Amplas Subdistrict. Having participated in this activity, the knowledge of mothers about the making of ingredients from Moringa leaves was increased and the knowledge of mothers about the benefits of Moringa leaves was also increased. Â Â